Bilateral angle closure glaucoma in a teenage girl - A rare presentation in Arab population - A case report: PACG in teenaged Arab girl - Alzuhairy, Sultan (International Journal of Health Sciences, 2019)
Primary angle closure glaucoma (PACG) usually presents as unilateral and has acute onset. In Arab population, the proportion of open- and closed-angle glaucoma is similar. To the best of our knowledge, chronic PACG in very young age is rare. We share a case report of a teenage girl with advanced glaucomatous changes and, on gonioscopy, had synechia and closed angle of anterior chamber. She was treated by bilateral laser iridotomy and topical glaucoma medication. The author concludes that, even at very young age, in the absence of predisposing factors for secondary glaucoma, the patient should be investigated for PACG and managed accordingly.